Mucocele Involving the Anterior Clinoid Process: MR and CT Findings - Tchoyoson Lim, C. C.; Dillon, William P.; McDermott, Michael W. (American Journal of Neuroradiology, 1999)
Summary: We report two patients with surgically proved mucoceles involving the anterior clinoid process. One patient had a mucocele of an Onodi cell and the other had a mucocele isolated to the anterior clinoid process. The MR signal was increased on both T1- and T2-weighted images in the first patient but was isointense on both sequences in the second patient, a finding that resulted in misdiagnosis. The developmental and anatomic features, as well as the diagnostic pitfalls, are discussed.